A importância dos investimentos públicos para os municípios recém emancipados: caso de João Costa/PI - Silva Neto, Vitorino Tavares da (2014)
The poverty of some areas of Brazil, like the northeast, has as one of its likely explanatory variables and the few poor investments in public sector in all its spheres. One of the policies that seek to possibly correct this distortion lies in the context of the political emancipation of municipalities, which the discourse propagated by the political class brings the government intervention in social demands, for example. The classic explanation is that the large territory of the municipalities hinders the resolution in combating these problems. From this hypothesis it was stipulated aim of this study verify the importance of public investment in municipalities newly emancipated, focusing on the city of João Costa located in the hinterland of the state of Piaui. As a methodology for this study using the literature search, consulting the statistics of social and economic context before and after the process of political emancipation. We conclude that the process of political emancipation provoked the scale of public investments in the region, contributing to the development of the city population by providing access to basic social, but still it was found a strong dependence on the economic dynamics of the local district public sector.